Manual of child Psychology / edited by Leonated Carmichael - "Carmichael, Leonard.( ed.)" (New Delhi, 1968)
It has been said that a most serious need of modern psychology is for advanced scientific manuals to bridge the gap between the excellent and carried elementary textbooks in this field and he scientific periodical literature of psychology. This manual is an advanced level textbook and is intended to be an addition at just this level to the literature of general as well as child psychology.
Keywords: Psychology